Long-term morphological and sedimentological changes caused by bottom trawling on the northern Catalan continental shelf (NW Mediterranean) - Durán, Ruth; Puig, Pere; Paradis, Sarah; Guillén, Jorge; Palanques, Albert; Lo Iacono, Claudio; Arjona-Camas, Marta; Muñoz, Araceli; Micallef, Aaron (Frontiers in Marine Science, 2023)
High-resolution multibeam echosounder data, side scan sonar, sediment grain size and vessel tracking data have been used to investigate the impact of bottom trawling on the seafloor morphology and surficial sediments of the northern Catalan continental shelf (NW Mediterranean). In this area, bottom trawling has been continuously practiced during several decades, providing new insights into the impact of this anthropogenic activity on the seafloor. Multibeam echosounder results evidenced the occurrence of large-scale erosive morphologies as a consequence of repeated scouring by fishing gears in localized areas. These morphologies are characterized by elongated (70-300 m wide and up to 8 km long) areas of high backscatter that correspond well with trawling effort. Side scan sonar data shows higher densities of trawl marks in the area of high backscatter than the surroundings. Some high backscatter areas show no discernible relief, while others appear in the bathymetric data as shallow elongated depressions of up to 1.2 m deep in the most impacted areas. Sediment cores crossing these features show an upward-coarsening trend in the first 4-5 cm of the core, suggesting that part of the finer fraction resuspended by trawling is winnowed, progressively increasing the sand content of the surface sediment. The identification of these large erosive morphologies in the main fishing grounds evidences that repeated trawling over the same fishing ground during decades can affect the seafloor at greater depths in the sediment column than previously observed, leading to more permanent morphological changes on the seafloor. Furthermore, the evolution of these erosive features over a 13-year interval points towards long recovery periods.